2013
DOI: 10.1111/apa.12434
|View full text |Cite
|
Sign up to set email alerts
|

Motivational interviewing improves exclusive breastfeeding in an Australian randomised controlled trial

Abstract: A motivational interviewing intervention by primary care health professionals who have undertaken a replicable training programme is feasible and effective in increasing exclusive breastfeeding and full/predominant breastfeeding at 4 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 19 publications
3
28
1
Order By: Relevance
“…A few studies have examined the effectiveness of BMIs to promote breastfeeding and have reported different findings. One study showed a significant increase in EBF rates at the fourth month (65% intervention group vs. 56% control group; odds ratio (OR): 1.9, 95% confidence interval (95% CI): 1.01–3.5, p = .047; Elliott‐Rudder, Pilotto, McIntyre, & Ramanathan, ). In contrast, two studies showed a duration of breastfeeding of only 8–18 days longer in the intervention groups without statistical significance (Wilhelm, Aguirre, Koehler, & Rodehorst, ; Wilhelm, Stepans, Hertzog, Rodehorst, & Gardner, ).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have examined the effectiveness of BMIs to promote breastfeeding and have reported different findings. One study showed a significant increase in EBF rates at the fourth month (65% intervention group vs. 56% control group; odds ratio (OR): 1.9, 95% confidence interval (95% CI): 1.01–3.5, p = .047; Elliott‐Rudder, Pilotto, McIntyre, & Ramanathan, ). In contrast, two studies showed a duration of breastfeeding of only 8–18 days longer in the intervention groups without statistical significance (Wilhelm, Aguirre, Koehler, & Rodehorst, ; Wilhelm, Stepans, Hertzog, Rodehorst, & Gardner, ).…”
Section: Introductionmentioning
confidence: 99%
“…Two of these RCTs 53,54 found no significant effect of MI. The other RCT 55 found statistically significant effects of MI on breastfeeding status at 2 and 4 months but not at 6 months post birth. In all three RCTs, it was difficult to disentangle the effects of MI from the other aspects of the intervention.…”
Section: Motivational Interviewingmentioning
confidence: 87%
“…There have been at least 12 systematic reviews that have found statistically significant effects of MI in relation to health outcomes [41][42][43][44][45][46][47][48][49][50][51][52] and three RCTs 53-55 examining MI and breastfeeding support. A health educator, 53 a research nurse 54 and a practice nurse 55 delivered the MI in the RCTs. Two of these RCTs 53,54 found no significant effect of MI.…”
Section: Motivational Interviewingmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming an effect size like those of previous studies (Elliott-Rudder et al, 2014;Pollard, 2011;Wilhelm et al, 2015Wilhelm et al, , 2006 and with common alpha risk of 0.05, beta risk of 0.20, and estimated loss to follow-up of 10%, a sample of n = 44 participants in each group will be required using a log-rank survival test. Assuming an effect size like those of previous studies (Elliott-Rudder et al, 2014;Pollard, 2011;Wilhelm et al, 2015Wilhelm et al, , 2006 and with common alpha risk of 0.05, beta risk of 0.20, and estimated loss to follow-up of 10%, a sample of n = 44 participants in each group will be required using a log-rank survival test.…”
Section: Sample Size Determinationmentioning
confidence: 99%